Resin composition, pellet, molded article, and composite
A resin composition with polybutylene terephthalate resin and specific nitrogen and titanium parameters, along with optional additives, addresses the need for high adhesive strength and reduced gas content in molded products, ensuring excellent mechanical properties.
Patent Information
- Application Number
- JP2024175062
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-04
- Filing Date
- 2024-10-04
- Publication Date
- 2025-04-16
AI Technical Summary
There is a need for a resin composition containing polybutylene terephthalate that achieves high adhesive strength with other components, especially when using an epoxy adhesive, while maintaining mechanical strength. Additionally, the composition should minimize gas content in the pellets post-production.
The resin composition incorporates a polybutylene terephthalate resin with a total nitrogen content of 0.1 to 3,000 ppm by mass and an active titanium parameter X of 25 or less. This composition may include an inorganic filler, a mold release agent, and a stabilizer, with the inorganic filler being a fibrous reinforcement.
The solution enables the production of molded products with excellent adhesion strength when bonded with an epoxy adhesive, while maintaining mechanical strength and reducing gas content in the pellets.
Smart Images

Figure 2025063870000001 
Figure 2025063870000002 
Figure 2025063870000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition, a pellet, a molded article, and a composite, and in particular to a resin composition containing a polybutylene terephthalate resin. [Background technology]
[0002] Polybutylene terephthalate resin is characterized by excellent mechanical properties, electrical properties, processing properties, and the like, and is widely used for various applications (Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2019 / 217680 [Patent Document 2] JP 2018-203932 A [Patent Document 3] International Publication No. 2020 / 246335 Summary of the Invention [Problem to be solved by the invention]
[0004] Here, for a resin composition containing a polybutylene terephthalate resin, high adhesive strength with other members is required depending on the application. In particular, a resin composition capable of providing a molded product having excellent adhesive strength with other members using an epoxy adhesive while maintaining mechanical strength is required.
[0005] On the other hand, it has been found that, depending on the type of polybutylene terephthalate resin, a large amount of gas may be contained in the pellets after production.
[0006] The present invention aims to solve these problems, and to provide a resin composition that has a low gas content in the pellets after production and that can provide a molded article that has excellent adhesive strength to other members using an epoxy-based adhesive while maintaining mechanical strength, as well as pellets, molded articles, and composites. [Means for solving the problem]
[0007] In view of the above problems, the present inventors have conducted research and found that the above problems can be solved by using a polybutylene terephthalate resin that has a large amount of nitrogen element and satisfies predetermined active titanium parameters.
[0008] Specifically, the above problems were solved by the following means.
[0009] <1-1> A composition comprising a polybutylene terephthalate resin and at least one selected from the group consisting of an inorganic filler, a release agent, and a stabilizer; The polybutylene terephthalate resin has a total nitrogen element content of 0.1 to 3000 ppm by mass, and an active titanium parameter X shown below of 25 or less.
[0010]
number
[0011]
number
[0012] <1-2> The inorganic filler is contained in an amount of 10 to 150 parts by mass relative to 100 parts by mass of the polybutylene terephthalate resin, The inorganic filler is a fibrous reinforcing material; The resin composition according to <1-1>.
[0013] <1-3> The resin composition according to <1-1> or <1-2>, which contains a release agent and / or a stabilizer.
[0014] <1-4> The resin composition according to any one of <1-1> to <1-3>, wherein the active titanium parameter X is 12 or less.
[0015] <1-5> The resin composition according to any one of <1-1> to <1-4>, wherein the polybutylene terephthalate resin contains titanium element in an amount of 30 to 500 ppm by mass.
[0016] <1-6> The resin composition according to any one of <1-1> to <1-5>, wherein the polybutylene terephthalate resin has a terminal carboxyl group concentration of 25 μmol / g or more.
[0017] <1-7> The resin composition according to any one of <1-1> to <1-6>, further comprising a recycled polyethylene terephthalate resin.
[0018] <1-8> The resin composition according to any one of <1-1> to <1-7>, wherein the polybutylene terephthalate resin has a total sulfur element content of 0.1 to 100 ppm by mass.
[0019] <1-9> The resin composition according to any one of <1-1> to <1-8>, wherein the polybutylene terephthalate resin has a terminal vinyl group concentration of 1 to 15 μmol / g.
[0020] <1-10> The resin composition according to any one of <1-1> to <1-9>, wherein the polybutylene terephthalate resin has dicarboxylic acid units and diol units, and 80 mol % or more of all dicarboxylic acid units are terephthalic acid units derived from fossil resources, and 80 mol % or more of all diol units are 1,4-butanediol units derived from fossil resources.
[0021] <1-11> The resin composition according to any one of <1-1> to <1-10>, wherein the polybutylene terephthalate resin has an Mw / Mn ratio of 2.1 or more.
[0022] <1-12> The resin composition according to any one of <1-1> to <1-11>, wherein the polybutylene terephthalate resin includes a recycled product.
[0023] <1-13> The resin composition according to any one of <1-1> to <1-12>, further comprising an epoxy compound.
[0024] <1-14> The inorganic filler is contained in an amount of 10 to 150 parts by mass relative to 100 parts by mass of the polybutylene terephthalate resin, The inorganic filler is a fibrous reinforcing material, Contains a release agent and / or a stabilizer, The active titanium parameter X is 12 or less; The polybutylene terephthalate resin contains titanium element in an amount of 30 to 500 ppm by mass, The polybutylene terephthalate resin has a terminal carboxyl group concentration of 25 μmol / g or more; In addition, it contains recycled polyethylene terephthalate resin, The polybutylene terephthalate resin has a total sulfur element content of 0.1 to 100 ppm by mass, The polybutylene terephthalate resin has a terminal vinyl group concentration of 1 to 15 μmol / g, The polybutylene terephthalate resin has dicarboxylic acid units and diol units, and 80 mol % or more of the total dicarboxylic acid units are terephthalic acid units, and 80 mol % or more of the total diol units are 1,4-butanediol units, The polybutylene terephthalate resin has an Mw / Mn ratio of 2.1 or more, The resin composition according to any one of <1-1> to <1-13>, wherein the polybutylene terephthalate resin includes a recycled product.
[0025] <1-15> The resin composition according to <1-14>, further comprising an epoxy compound.
[0026] <1-16> The resin composition according to <1-14> or <1-15>, wherein the polybutylene terephthalate resin has dicarboxylic acid units and diol units, and 80 mol % or more of the total dicarboxylic acid units are terephthalic acid units derived from fossil resources, and 80 mol % or more of the total diol units are 1,4-butanediol units derived from fossil resources.
[0027] <1-17> The resin composition according to any one of <1-1> to <1-16>, which is for use in bonding with an epoxy adhesive.
[0028] <1-18> A pellet of the resin composition according to any one of <1-1> to <1-17>.
[0029] <1-19> A molded article molded from the resin composition according to any one of <1-1> to <1-17>.
[0030] Molded articles made from the pellets described in <1-20> and <1-18>.
[0031] <1-21> A composite comprising the molded article according to <1-19> or <1-20> and an adhesive layer, the adhesive layer containing an epoxy-based adhesive.
[0032] <2-1> A composition comprising 10 to 150 parts by mass of a fibrous reinforcing material relative to 100 parts by mass of polybutylene terephthalate resin, The polybutylene terephthalate resin has a total nitrogen element content of 1 to 3000 ppm by mass.
[0033] <2-2> The resin composition according to <2-1>, wherein the polybutylene terephthalate resin has a total sulfur element content of 1 to 100 ppm by mass.
[0034] <2-3> The resin composition according to <2-1> or <2-2>, wherein the polybutylene terephthalate resin has a terminal vinyl group concentration of 1 to 15 μmol / g.
[0035] <2-4> The resin composition according to any one of <2-1> to <2-3>, wherein the polybutylene terephthalate resin has dicarboxylic acid units and diol units, and 80 mol % or more of all dicarboxylic acid units are terephthalic acid units derived from fossil resources, and 80 mol % or more of all diol units are 1,4-butanediol units derived from fossil resources.
[0036] <2-5> The resin composition according to any one of <2-1> to <2-4>, wherein the polybutylene terephthalate resin has an Mw / Mn ratio of 2.1 or more.
[0037] <2-6> The resin composition according to any one of <2-1> to <2-5>, wherein the polybutylene terephthalate resin contains a recycled product.
[0038] <2-7> The resin composition according to any one of <2-1> to <2-6>, further comprising an epoxy compound.
[0039] <2-8> The polybutylene terephthalate resin has a total sulfur element content of 1 to 100 ppm by mass, The polybutylene terephthalate resin has a terminal vinyl group concentration of 1 to 15 μmol / g, The polybutylene terephthalate resin has dicarboxylic acid units and diol units, and 80 mol % or more of the total dicarboxylic acid units are terephthalic acid units, and 80 mol % or more of the total diol units are 1,4-butanediol units, The polybutylene terephthalate resin has an Mw / Mn ratio of 2.1 or more, The resin composition according to any one of <2-1> to <2-7>, wherein the polybutylene terephthalate resin includes a recycled product.
[0040] <2-9> The resin composition according to <2-8>, further comprising an epoxy compound.
[0041] <2-10> The resin composition according to <2-8> or <2-9>, wherein the polybutylene terephthalate resin has dicarboxylic acid units and diol units, and 80 mol % or more of the total dicarboxylic acid units are terephthalic acid units derived from fossil resources, and 80 mol % or more of the total diol units are 1,4-butanediol units derived from fossil resources.
[0042] <2-11> The resin composition according to any one of <2-1> to <2-10>, which is for use in bonding with an epoxy adhesive.
[0043] <2-12> Pellets of the resin composition according to any one of <2-1> to <2-11>.
[0044] <2-13> A molded article made from the resin composition according to any one of <2-1> to <2-11>.
[0045] <2-14> Molded products made from the pellets described in <2-12>.
[0046] <2-15> A composite comprising the molded article according to <2-13> or <2-14> and an adhesive layer, the adhesive layer containing an epoxy-based adhesive. Effect of the Invention
[0047] The present invention makes it possible to provide a resin composition that has a low gas content in the pellets after production and that can provide molded articles that have excellent adhesive strength to other members using an epoxy-based adhesive while maintaining mechanical strength, as well as pellets, molded articles, and composites. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0048] The resin composition of the present embodiment contains a polybutylene terephthalate resin and at least one selected from the group consisting of an inorganic filler, a release agent, and a stabilizer, and the polybutylene terephthalate resin is characterized in that the total nitrogen element amount is 0.1 to 3000 mass ppm and the active titanium parameter X shown below is 25 or less. By adopting such a constitution, a resin composition can be obtained that has a low gas content in the pellets after production, maintains mechanical strength, and can provide a molded product that has excellent adhesive strength with other members using an epoxy adhesive.
[0049]
number
[0050]
number
[0051] <Polybutylene terephthalate resin> The resin composition of the present embodiment contains a polybutylene terephthalate resin having a total nitrogen content of 0.1 to 3000 ppm by mass. By using such a polybutylene terephthalate resin, the adhesive strength with an epoxy adhesive can be increased.
[0052] In the polybutylene phthalate resin used in this embodiment, the total nitrogen element amount is 0.1 mass ppm or more, preferably 1 mass ppm or more, more preferably 2 mass ppm or more, even more preferably 3 mass ppm or more, and even more preferably 4 mass ppm or more, and is 3000 mass ppm or less, preferably 2500 mass ppm or less, more preferably 2000 mass ppm or less, even more preferably 1000 mass ppm or less, even more preferably 50 mass ppm or less, even more preferably 20 mass ppm or less, and especially more preferably 10 mass ppm or less. By making it equal to or more than the lower limit, the adhesive strength of the adhesive tends to be improved. Also, by making it equal to or less than the upper limit, the color tone change tends to be small.
[0053] The total nitrogen element content is measured according to the description in the Examples section below.
[0054] The polybutylene terephthalate resin used in this embodiment also has an active titanium parameter X shown below of 25 or less.
[0055]
number
[0056]
number
[0057] Titanium catalysts are added when synthesizing polybutylene terephthalate resin. However, it has been found that when titanium catalyst activity is high in the polybutylene terephthalate resin after polymerization, tetrahydrofuran derived from butanediol tends to be generated. In particular, in the case of industrial mass production, extrusion is performed continuously for a long time using a large extruder, and in such a case, tetrahydrofuran tends to be generated more easily.
[0058] In this embodiment, it is presumed that the use of the polybutylene terephthalate resin (T) having low titanium activity effectively suppresses the generation of tetrahydrofuran gas in the molded product.
[0059] Furthermore, the resin composition of the present embodiment may contain, in addition to the polybutylene terephthalate resin (T), a polybutylene terephthalate resin (N) other than the polybutylene terephthalate resin (T).
[0060] In this specification, unless otherwise specified, the polybutylene terephthalate resin is meant to include both polybutylene terephthalate resin (T) and polybutylene terephthalate resin (N).
[0061] The active titanium parameter X of the polybutylene terephthalate resin used in this embodiment is 25 or less, preferably 20 or less, more preferably 15 or less, even more preferably 12 or less, and even more preferably 10 or less. The lower limit of the active titanium parameter X of the polybutylene terephthalate resin is preferably 0, but even if it is 1 or more, the required performance is sufficiently satisfied.
[0062] When two or more polybutylene terephthalate resins are used, it is preferable that the polybutylene terephthalate resin with the largest content satisfies the above active titanium parameters, and it is more preferable that all of the polybutylene terephthalate resins satisfy the above active titanium parameters.
[0063] A polybutylene terephthalate resin synthesized using a titanium catalyst and having a low active titanium parameter X can be obtained, for example, by the following method.
[0064] (1) Increasing the concentration of metal elements such as sodium and calcium in the polybutylene terephthalate resin. These metal elements tend to reduce the activity of the titanium catalyst.
[0065] (2) Increase the amount of alkaline components in the polybutylene terephthalate resin. Titanium catalysts are acid catalysts, so their activity tends to decrease in the presence of alkaline components.
[0066] (3) Increasing the terminal carboxylic acid concentration of the polybutylene terephthalate resin.
[0067] (4) Use recycled polybutylene terephthalate resin. In particular, material recycled polybutylene terephthalate resin tends to have low titanium catalyst activity.
[0068] α=X / M...Equation (3) (In formula (3), X is the active titanium parameter, and [M] is the titanium element concentration (ppm by mass) in the polybutylene terephthalate resin.)
[0069] The evaluation of the change in the terminal carboxyl group concentration over time is performed under a nitrogen atmosphere to prevent the influence of oxygen. In addition, if the water concentration in the polybutylene terephthalate resin to be evaluated is high, hydrolysis reactions occur frequently, making it difficult to accurately grasp the decomposition behavior involving catalytic activity not due to hydrolysis, so the water concentration is preferably low and is performed at 300 mass ppm or less. The temperature is 245°C. Under such heat treatment conditions, the decrease in number average molecular weight due to reactions other than the hydrolysis reaction caused by the water contained in the polybutylene terephthalate resin can be ignored, and the increase in the terminal carboxyl group concentration due to the hydrolysis reaction can be considered to be equal to the increase in the terminal hydroxyl group concentration before and after the heat treatment, so the change in the terminal carboxyl group concentration due to thermal decomposition reactions other than the hydrolysis reaction is calculated using the following formula (4).
[0070] Formula (4)
number
[0071] The titanium element concentration in the polybutylene terephthalate resin used in this embodiment is preferably 30 ppm by mass or more, may be 35 ppm by mass or more, may be 40 ppm by mass or more, may be 45 ppm by mass or more, may be 50 ppm by mass or more, may be 55 ppm by mass or more, may be 60 ppm by mass or more, may be 65 ppm by mass or more, may be 70 ppm by mass or more, may be 75 ppm by mass or more, and is preferably 500 ppm by mass or less, may be 400 ppm by mass or less, may be 300 ppm by mass or less, may be 150 ppm by mass or less, may be 120 ppm by mass or less, may be 110 ppm by mass or less, may be 100 ppm by mass or less, may be 90 ppm by mass or less, or may be 80 ppm by mass or less.
[0072] The titanium element content is measured according to the description in the Examples section below.
[0073] In the polybutylene phthalate resin used in this embodiment, the total sulfur element content is preferably 0.1 mass ppm or more, more preferably 1 mass ppm or more, even more preferably 2 mass ppm or more, even more preferably 4 mass ppm or more, even more preferably 7 mass ppm or more, and also preferably 100 mass ppm or less, more preferably 80 mass ppm or less, even more preferably 60 mass ppm or less, even more preferably 40 mass ppm or less, even more preferably 25 mass ppm or less, even more preferably 20 mass ppm or less, and particularly more preferably 15 mass ppm or less. By making it equal to or more than the lower limit, the adhesive strength of the adhesive tends to be improved. Also, by making it equal to or less than the upper limit, the decomposition gas tends to be reduced.
[0074] The total amount of elemental sulfur is measured according to the description in the Examples section below.
[0075] In the polybutylene phthalate resin used in this embodiment, the total amount of nitrogen element and sulfur element is, for example, 0.2 mass ppm or more, preferably 0.5 mass ppm or more, preferably 1 mass ppm or more, preferably 2 mass ppm or more, more preferably 5 mass ppm or more, even more preferably 10 mass ppm or more, even more preferably 12 mass ppm or more, and preferably 120 mass ppm or less, more preferably 100 mass ppm or less, even more preferably 60 mass ppm or less, even more preferably 40 mass ppm or less, even more preferably 30 mass ppm or less, even more preferably 25 mass ppm or less, and especially more preferably 20 mass ppm or less. By making it equal to or more than the lower limit, the adhesive strength of the adhesive tends to be further improved. Also, by making it equal to or less than the upper limit, the decomposition gas or color change tends to be reduced.
[0076] Such polybutylene terephthalate resins having a high total nitrogen or sulfur content may be prepared by blending a nitrogen source or a sulfur source (nitrogen or sulfur element itself, or a resin additive containing nitrogen or sulfur element) with virgin polybutylene terephthalate resin, or by using recycled polybutylene terephthalate resin. In recycled polybutylene terephthalate resins, resin additives such as lubricants, release agents, and antioxidants remain, and the nitrogen source or sulfur source derived from these can be effectively utilized.
[0077] In particular, in this embodiment, polybutylene terephthalate resin obtained from recycled products derived from connector parts and the like is preferred because the total nitrogen element content often falls within the desired range.
[0078] The calcium element concentration of the polybutylene terephthalate resin used in this embodiment is preferably 0.1 mass ppm or more, more preferably 1 mass ppm or more, more preferably 3 mass ppm or more, even more preferably 5 mass ppm or more, even more preferably 7 mass ppm or more, and also preferably 3000 mass ppm or less, preferably 2500 mass ppm or less, preferably 2000 mass ppm or less, preferably 1000 mass ppm or less, more preferably 500 mass ppm or less, even more preferably 300 mass ppm or less, even more preferably 200 mass ppm or less, and may be 100 mass ppm or less, 50 mass ppm or less, 30 mass ppm or less, or 10 mass ppm or less. By making it equal to or more than the lower limit, the transesterification reaction tends to be more effectively suppressed. In addition, by making it equal to or more than the lower limit, the generation of tetrahydrofuran gas tends to be more effectively suppressed. In addition, by making it equal to or less than the upper limit, the alkali decomposition resistance tends to be further improved.
[0079] The calcium element in the polybutylene terephthalate resin is derived from, for example, an inorganic filler of an inorganic filler.
[0080] The titanium element concentration, sodium element concentration, and calcium element concentration are measured according to the description in the Examples section described later.
[0081] The terminal vinyl group concentration of the polybutylene terephthalate resin is preferably 50 μmol / g or less, more preferably 15 μmol / g or less, even more preferably 12 μmol / g or less, even more preferably 10 μmol / g or less, even more preferably 8 μmol / g or less, and preferably 1 μmol / g or more, more preferably 2 μmol / g or more, and even more preferably 3 μmol / g or more. By making it below the upper limit, the terminal hydroxyl group concentration and terminal carboxyl group concentration are relatively high, and the adhesion with the epoxy adhesive tends to be improved. Also, by making it above the lower limit, the terminal hydroxyl group concentration and terminal carboxyl group concentration are relatively low, and the reactivity with other resins such as polycarbonate and epoxy resin is suppressed, the thickening effect is small, and the flowability tends to be improved.
[0082] When the resin composition of the present embodiment contains two or more types of polybutylene terephthalate resins, the terminal vinyl group concentration of the mixture is preferably within the above range.
[0083] The terminal vinyl group concentration of the polybutylene terephthalate resin is measured according to the description in the Examples section described later.
[0084] A polybutylene terephthalate resin having such a terminal vinyl group concentration can be obtained by increasing the number of times the polybutylene terephthalate resin is subjected to heat history, for example, by increasing the number of times it is melt-kneaded.
[0085] In the resin composition of the present embodiment, the terminal carboxyl group concentration (acid value) of the polybutylene terephthalate resin is preferably 100 μmol / g or less (μeq / g), more preferably 80 μmol / g or less, more preferably 70 μmol / g or less, even more preferably 60 μmol / g or less, even more preferably 40 μmol / g or less, even more preferably 30 μmol / g or less, and also preferably 10 μmol / g or more, more preferably 20 μmol / g or more, even more preferably 25 μmol / g or more, and even more preferably 27 μmol / g or more. By making it equal to or less than the upper limit, the hydrolysis resistance tends to be excellent. Also, by making it equal to or less than the upper limit, the hydrolysis resistance tends to be improved and the storage stability tends to be more excellent. On the other hand, by making it equal to or more than the lower limit, the adhesive strength to the adhesive tends to be further improved. Also, by making it equal to or more than the lower limit, the crystallization temperature Tc during cooling tends to be improved.
[0086] When the resin composition of the present embodiment contains two or more types of polybutylene terephthalate resins, the terminal carboxyl group concentration of the mixture is preferably within the above range.
[0087] The terminal carboxyl group concentration of the polybutylene terephthalate resin is measured according to the description in the Examples section described later.
[0088] A polybutylene terephthalate resin having such a concentration of terminal carboxyl groups can be obtained by, for example, subjecting the resin to a thermal history of a temperature equal to or higher than the melting point, such as by melt kneading.
[0089] In the resin composition of this embodiment, the terminal hydroxyl group concentration of the polybutylene terephthalate resin is preferably 110 μmol / g or less, more preferably 100 μmol / g or less, even more preferably 95 μmol / g or less, and preferably 30 μmol / g or more, more preferably 35 μmol / g or more, even more preferably 40 μmol / g or more, even more preferably 50 μmol / g or more, and even more preferably 70 μmol / g or more. By making it below the upper limit, the transesterification reaction is suppressed during melt-kneading with other resins such as polycarbonate, and the molding cycle is shortened. Also, by making it above the lower limit, the adhesive strength to the adhesive tends to be further improved.
[0090] When the resin composition of the present embodiment contains two or more types of polybutylene terephthalate resins, the terminal hydroxy group concentration of the mixture is preferably within the above range.
[0091] The terminal hydroxyl group concentration of the polybutylene terephthalate resin is measured according to the description in the Examples section described later.
[0092] A polybutylene terephthalate resin having such a terminal hydroxyl group concentration can be obtained by, for example, subjecting the resin to a thermal history of a temperature equal to or higher than the melting point, such as by melt kneading.
[0093] The intrinsic viscosity of the polybutylene terephthalate resin is preferably 0.60 dL / g or more, more preferably 0.70 dL / g or more, even more preferably 0.80 dL / g or more, and even more preferably 0.85 dL / g or more. By making it equal to or greater than the lower limit, there is a tendency that the deterioration of physical properties such as strength can be effectively suppressed. In addition, the intrinsic viscosity of the polybutylene terephthalate resin is preferably 1.30 dL / g or less, more preferably 1.10 dL / g or less, even more preferably 1.00 dL / g or less, and even more preferably 0.90 dL / g or less. By making it equal to or less than the upper limit, there is a tendency that the deterioration of fluidity can be effectively suppressed.
[0094] The intrinsic viscosity is measured by the following method.
[0095] Polybutylene terephthalate resin pellets are dissolved in a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (mass ratio 1 / 1) by stirring at 110°C for 1 hour to a concentration of 1.00 g / dL. The solution is then cooled to 30°C. Using a fully automatic solution viscometer, the number of seconds it takes for the sample solution and the solvent alone to fall at 30°C are measured, and the intrinsic viscosity is calculated using the formula:
[0096] Intrinsic viscosity=((1+4K H η sp ) 0.5 -1) / (2K H C) Here, η sp = η / η0-1, where η is the time it takes for the sample solution to fall, η0 is the time it takes for the solvent alone to fall, C is the concentration of the sample solution (g / dL), and K H is Huggins' constant. K H was set to 0.33.
[0097] The fully automatic solution viscometer used is a product of Shibayama Scientific Co., Ltd.
[0098] When the resin composition of the present embodiment contains two or more types of polybutylene terephthalate resins, the intrinsic viscosity is the intrinsic viscosity of the mixture.
[0099] The polybutylene terephthalate resin used in the resin composition of this embodiment is a polyester resin having a structure in which terephthalic acid units and 1,4-butanediol units are ester-bonded, and includes, in addition to polybutylene terephthalate resin (homopolymer), a polybutylene terephthalate copolymer containing other copolymerization components other than terephthalic acid units and 1,4-butanediol units, and a mixture of a homopolymer and a polybutylene terephthalate copolymer.
[0100] The polybutylene terephthalate resin may contain one or more types of dicarboxylic acid units other than terephthalic acid.
[0101] Specific examples of other dicarboxylic acids include aromatic dicarboxylic acids such as isophthalic acid, orthophthalic acid, 1,5-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, biphenyl-2,2'-dicarboxylic acid, biphenyl-3,3'-dicarboxylic acid, biphenyl-4,4'-dicarboxylic acid, bis(4,4'-carboxyphenyl)methane, anthracenedicarboxylic acid, and 4,4'-diphenyletherdicarboxylic acid; alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid and 4,4'-dicyclohexyldicarboxylic acid; and aliphatic dicarboxylic acids such as adipic acid, sebacic acid, azelaic acid, and dimer acid.
[0102] In the polybutylene terephthalate resin used in this embodiment, terephthalic acid units preferably account for 80 mol % or more of all dicarboxylic acid units, more preferably 90 mol % or more, even more preferably 95 mol % or more, and may even account for 99 mol % or more.
[0103] The diol unit may contain one or more other diol units in addition to 1,4-butanediol.
[0104] Specific examples of other diol units include aliphatic or alicyclic diols having 2 to 20 carbon atoms, bisphenol derivatives, etc. Specific examples include ethylene glycol, propylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, decamethylene glycol, cyclohexanedimethanol, 4,4'-dicyclohexylhydroxymethane, 4,4'-dicyclohexylhydroxypropane, ethylene oxide adduct diol of bisphenol A, etc. In addition to the above-mentioned bifunctional monomers, a small amount of a trifunctional monomer such as trimellitic acid, trimesic acid, pyromellitic acid, pentaerythritol, trimethylolpropane, etc., can be used in combination to introduce a branched structure, or a monofunctional compound such as a fatty acid, etc., can be used in combination to adjust the molecular weight.
[0105] In the polybutylene terephthalate resin used in this embodiment, 1,4-butanediol units preferably account for 80 mol % or more of all diol units, more preferably 90 mol % or more, even more preferably 95 mol % or more, and may even be 99 mol % or more.
[0106] As described above, the polybutylene terephthalate resin is preferably a polybutylene terephthalate homopolymer obtained by polycondensation of terephthalic acid and 1,4-butanediol. In addition, it may be a polybutylene terephthalate copolymer containing one or more dicarboxylic acids other than the terephthalic acid as the carboxylic acid unit and / or one or more diols other than the 1,4-butanediol as the diol unit. When the polybutylene terephthalate resin is a polybutylene terephthalate resin modified by copolymerization, specific preferred copolymers include polyester ether resins copolymerized with polyalkylene glycols, particularly polytetramethylene glycol, dimer acid copolymerized polybutylene terephthalate resins, and isophthalic acid copolymerized polybutylene terephthalate resins. Among them, it is preferable to use a polyester ether resin copolymerized with polytetramethylene glycol.
[0107] In addition, when the polybutylene terephthalate resin is a copolymer, the copolymerization amount is 1 mol% or more and less than 50 mol% of all polybutylene terephthalate resin units. In particular, the copolymerization amount is preferably 2 mol% or more and less than 50 mol%, more preferably 3 to 40 mol%, and further preferably 5 to 20 mol%. By setting the copolymerization ratio in this manner, it is preferable because a molded product having a small mold shrinkage rate and high impact resistance can be obtained.
[0108] In particular, the polybutylene terephthalate resin used in this embodiment has dicarboxylic acid units and diol units, and it is preferable that 80 mol % or more (preferably 90 mol % or more, more preferably 95 mol % or more, and even more preferably 99 mol % or more) of the total dicarboxylic acid units are terephthalic acid units derived from fossil resources, and 80 mol % or more (preferably 90 mol % or more, more preferably 95 mol % or more, and even more preferably 99 mol % or more) of the total diol units are 1,4-butanediol units derived from fossil resources.
[0109] In addition, the polybutylene terephthalate resin used in the present embodiment is preferably not a bio-polybutylene terephthalate resin. An example of a bio-polybutylene terephthalate resin is a polybutylene terephthalate resin in which 10% by mass or more, further 30% by mass or more, and 90% by mass or less, further 60% by mass or less of the total amount of dicarboxylic acid and diol, which are raw materials of the polybutylene terephthalate resin, are bio-derived raw materials.
[0110] The polybutylene terephthalate resin used in the present embodiment preferably has a high degree of dispersion. A high degree of dispersion increases the amount of terminal groups (particularly the amount of terminal hydroxyl groups and / or the amount of terminal carboxyl groups) of the polybutylene terephthalate resin, and can further improve adhesion to an epoxy adhesive.
[0111] The polybutylene terephthalate resin preferably has an Mw / Mn of 2.1 or more, more preferably 2.2 or more, and even more preferably 2.3 or more, and preferably 3.5 or less, more preferably 3.0 or less, even more preferably 2.7 or less, even more preferably 2.6 or less, and even more preferably 2.5 or less. By making it equal to or more than the lower limit, the adhesive strength to the epoxy adhesive tends to be improved. Also, by making it equal to or less than the upper limit, the mechanical strength tends to be improved.
[0112] Such a polybutylene terephthalate resin with a high degree of dispersion can be obtained by increasing the number of times the polybutylene terephthalate resin is subjected to thermal history, for example, by increasing the number of times it is melt-kneaded, or by blending two or more types of polybutylene terephthalate resins having different average molecular weights.
[0113] The number average molecular weight (Mn) of the polybutylene terephthalate resin used in this embodiment is preferably 2500 or more, more preferably 3000 or more, even more preferably 3500 or more, even more preferably 3700 or more, even more preferably 4000 or more, and preferably 20000 or less, more preferably 18000 or less, even more preferably 14000 or less, even more preferably 10000 or less, and even more preferably 6000 or less. By making it equal to or more than the lower limit, the mechanical strength tends to be excellent. Also, by making it equal to or less than the upper limit, the fluidity of the resin tends to be improved.
[0114] The weight average molecular weight (Mw) of the polybutylene terephthalate resin used in this embodiment is preferably 5000 or more, more preferably 6000 or more, even more preferably 7000 or more, even more preferably 8000 or more, even more preferably 9500 or more, and preferably 40000 or less, more preferably 35000 or less, even more preferably 30000 or less, even more preferably 25000 or less, and even more preferably 20000 or less. By making it equal to or more than the lower limit, the mechanical strength tends to be improved. Also, by making it equal to or less than the upper limit, the fluidity of the resin tends to be improved.
[0115] The number average molecular weight and weight average molecular weight of the polybutylene terephthalate resin are measured according to the description in the Examples section described later.
[0116] The melting point (Tm) of the polybutylene terephthalate resin used in this embodiment measured according to DSC is preferably 200°C or higher, more preferably 205°C or higher, even more preferably 210°C or higher, even more preferably 215°C or higher, even more preferably 220°C or higher, and preferably 280°C or lower, more preferably 270°C or lower, even more preferably 260°C or lower, even more preferably 255°C or lower, and even more preferably 240°C or lower. By making it equal to or higher than the lower limit, the heat resistance tends to be further improved. Also, by making it equal to or lower than the upper limit, the molding cycle tends to be further improved.
[0117] When the resin composition of the present embodiment contains two or more polyalkylene terephthalate resins, the melting point is the melting point of the mixture. When multiple melting point peaks are detected, at least one of the multiple melting points may be included in the range above the lower limit and below the upper limit, but it is preferable that the component with the highest content among the multiple melting points is included in the range above the lower limit and below the upper limit, and it is more preferable that all of the multiple melting points are included in the range above the lower limit and below the upper limit.
[0118] The crystallization temperature (Tc) of the polybutylene terephthalate resin used in this embodiment measured according to DSC is preferably 130°C or higher, more preferably 145°C or higher, even more preferably 160°C or higher, even more preferably 175°C or higher, even more preferably 190°C or higher, and preferably 240°C or lower, more preferably 230°C or lower, even more preferably 220°C or lower, even more preferably 210°C or lower, and even more preferably 200°C or lower. By setting it to the lower limit or higher, the solidification speed tends to be improved and the molding cycle tends to be further improved. Also, by setting it to the upper limit or lower, the appearance of the molded product tends to be improved.
[0119] When the resin composition of the present embodiment contains two or more polyalkylene terephthalate resins, the crystallization temperature is the crystallization temperature of the mixture.When multiple peaks of crystallization temperature are detected, at least one of the multiple crystallization temperatures may be included in the range of the lower limit or more and the upper limit or less, but among the multiple crystallization temperatures, it is preferable that the component with a large content is included in the range of the lower limit or more and the upper limit or less, and it is more preferable that all of the multiple crystallization temperatures are included in the range of the lower limit or more and the upper limit or less.
[0120] The Tm and Tc of the polyalkylene terephthalate resin are measured according to the method described in the Examples below.
[0121] The polybutylene terephthalate resin used in the present embodiment may be a recycled product.
[0122] Examples of recycled polybutylene terephthalate resin include those obtained by material recycling in which molded products of recovered used polybutylene terephthalate resin are crushed, washed, and reused, and those obtained by chemical recycling (chemical decomposition method). In this embodiment, material recycled products are preferred.
[0123] In this embodiment, in particular, recycled polybutylene terephthalate resins with many heat histories can be used. Heat histories include melt kneading, and thermoforming such as injection molding and extrusion molding. In this embodiment, polybutylene terephthalate resins with 3 to 10 heat histories can be used.
[0124] Examples of such recycled products include connectors, home appliances, toothbrushes, textiles, miscellaneous goods, automobile parts, films, tubes, and other extruded parts.
[0125] Polybutylene terephthalate resin, particularly recycled polybutylene terephthalate resin, may contain metal elements as impurities, which may come from the reactor or cutters used during pulverization or pelletization.
[0126] The amount of iron element in the polybutylene terephthalate resin used in this embodiment is preferably 0.1 μg / g or more, and is preferably 100 μg / g or less, more preferably 70 μg / g or less, even more preferably 50 μg / g or less, even more preferably 10 μg / g or less, and even more preferably 5 μg / g or less.
[0127] The amount of aluminum element in the polybutylene terephthalate resin used in this embodiment is preferably 0.1 μg / g or more, and is preferably 100 μg / g or less, more preferably 70 μg / g or less, even more preferably 50 μg / g or less, even more preferably 10 μg / g or less, and even more preferably 5 μg / g or less.
[0128] The amounts of iron element and aluminum element in the polybutylene terephthalate resin are measured according to the method described in the Examples below.
[0129] The content of the polybutylene terephthalate resin in the resin composition of the present embodiment is preferably 30% by mass or more, more preferably 50% by mass or more, even more preferably 60% by mass or more, and even more preferably 65% by mass or more, based on 100% by mass of the resin composition. The content of the polybutylene terephthalate resin is preferably 85% by mass or less, more preferably 80% by mass or less, and even more preferably 75% by mass or less.
[0130] The resin composition of the present embodiment may contain only one type of polybutylene terephthalate resin, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0131] <Inorganic filler> The resin composition of the present embodiment may contain an inorganic filler. By containing an inorganic filler, the mechanical strength of the obtained molded article can be improved.
[0132] As the inorganic filler, fibrous reinforcing materials, which will be described in detail later, granular or amorphous inorganic fillers such as calcium carbonate, titanium oxide, feldspar minerals, clay, and glass beads, plate-like inorganic fillers such as talc, and scale-like inorganic fillers such as glass flakes, mica, and graphite can be used. Among them, fibrous reinforcing materials are preferred from the viewpoints of mechanical strength and heat resistance. As the glass fiber, either a round cross-sectional shape or an irregular cross-sectional shape can be used.
[0133] The fibrous reinforcing agent is a fibrous material that has the effect of improving the mechanical properties of the resin composition obtained by blending it with a resin, and a wide range of commonly used fibrous reinforcing agents for plastics can be used.
[0134] Raw materials for the fibrous reinforcing material include inorganic substances such as glass, carbon (carbon fiber, etc.), alumina, boron, ceramics, and metals (steel, etc.), and organic substances such as plants (including kenaf, bamboo, etc.), aramid, polyoxymethylene, aromatic polyamide, polyparaphenylene benzobisoxazole, and ultra-high molecular weight polyethylene, with glass being preferred.
[0135] The glass fibers are selected from glass compositions such as A-glass, C-glass, E-glass, R-glass, D-glass, M-glass, and S-glass, with E-glass (alkali-free glass) being particularly preferred.
[0136] Glass fiber refers to a fibrous material whose cross section cut perpendicularly to the length direction has a perfect circle or polygonal shape. The number average fiber diameter of the single fiber of the glass fiber is usually 1 to 25 μm, preferably 5 to 17 μm. By making the number average fiber diameter 1 μm or more, the moldability of the resin composition tends to be improved. By making the number average fiber diameter 25 μm or less, the appearance of the obtained structure tends to be improved, and the reinforcing effect also tends to be improved. The glass fiber may be a single fiber or a plurality of single fibers twisted together.
[0137] The form of the glass fiber may be any of glass rovings obtained by continuously winding single fibers or multiple twisted fibers, chopped strands cut to a length of 1 to 10 mm (i.e., glass fibers having a number average fiber length of 1 to 10 mm), milled fibers pulverized to a length of about 10 to 500 μm (i.e., glass fibers having a number average fiber length of 10 to 500 μm), etc., but chopped strands cut to a length of 1 to 10 mm are preferred. Glass fibers of different forms can also be used in combination.
[0138] Glass fibers having an irregular cross-sectional shape are also preferred. The irregular cross-sectional shape has an aspect ratio, which is the long axis / short axis ratio of a cross section perpendicular to the longitudinal direction of the fiber, of, for example, 1.5 to 10, preferably 2.5 to 10, more preferably 2.5 to 8, and even more preferably 2.5 to 5.
[0139] The glass fiber may be surface-treated with, for example, a silane-based compound, an epoxy-based compound, a urethane-based compound, or the like, or may be oxidized, in order to improve its affinity with the resin component, as long as this does not significantly impair the properties of the resin composition in this embodiment.
[0140] The content of the inorganic filler (preferably a fibrous reinforcing material, more preferably glass fiber) in the resin composition of this embodiment is preferably 10 parts by mass or more, more preferably 15 parts by mass or more, even more preferably 20 parts by mass or more, and even more preferably 35 parts by mass or more, relative to 100 parts by mass of polybutylene terephthalate resin. By making it equal to or more than the lower limit, the mechanical strength of the obtained molded article tends to be further increased. In addition, the content of the inorganic filler (preferably a fibrous reinforcing material, more preferably glass fiber) is preferably 150 parts by mass or less, more preferably 140 parts by mass or less, even more preferably 120 parts by mass or less, even more preferably 100 parts by mass or less, even more preferably 80 parts by mass or less, even more preferably 70 parts by mass or less, even more preferably 60 parts by mass or less, even more preferably 50 parts by mass or less, and may be 45 parts by mass or less. By making it equal to or less than the upper limit, the appearance of the obtained molded article tends to be further improved.
[0141] The content of the inorganic filler (preferably a fibrous reinforcing material, more preferably glass fiber) in the resin composition in this embodiment is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and even more preferably 25% by mass or more, in 100% by mass of the resin composition. In addition, the content of the inorganic filler (preferably a fibrous reinforcing material, more preferably glass fiber) in the resin composition is more preferably 60% by mass or less, even more preferably 55% by mass or less, even more preferably 45% by mass or less, even more preferably 40% by mass or less, and even more preferably 35% by mass or less. By making it equal to or more than the lower limit, the mechanical strength tends to be further increased. In addition, by making it equal to or less than the upper limit, the appearance of the obtained molded product tends to be further improved.
[0142] The resin composition in this embodiment may contain only one type of inorganic filler (preferably a fibrous reinforcing material, more preferably glass fiber), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.
[0143] <Epoxy compounds> The resin composition of the present embodiment may contain an epoxy compound. By containing an epoxy compound, the hydrolysis resistance of the obtained molded article tends to be improved, and the adhesiveness with an epoxy adhesive tends to be improved, which is preferable.
[0144] The epoxy compound may be a monofunctional epoxy compound or a polyfunctional epoxy compound, but a polyfunctional epoxy compound is preferred.As the polyfunctional epoxy compound, for example, bisphenol A type epoxy compound, bisphenol F type epoxy compound, resorcin type epoxy compound, novolac type epoxy compound, alicyclic compound type diepoxy compound, glycidyl ethers, epoxidized polybutadiene, more specifically, bisphenol A type epoxy compound, bisphenol F type epoxy compound, resorcin type epoxy compound, novolac type epoxy compound, vinylcyclohexene dioxide, dicyclopentadiene oxide, and other alicyclic compound type epoxy compounds can be preferably used.Among them, bisphenol A type epoxy compound and novolac type epoxy compound are more preferred.
[0145] The epoxy compound may also be a copolymer containing a glycidyl group-containing compound as a constituent component, such as a copolymer of a glycidyl ester of an α,β-unsaturated acid and one or more monomers selected from the group consisting of an α-olefin, acrylic acid, an acrylic acid ester, methacrylic acid, a methacrylic acid ester, and styrene.
[0146] The epoxy compound is preferably a copolymer of an epoxy group-containing monomer and a styrene-based monomer, and may be a copolymer of other copolymerizable monomers. Examples of the styrene-based monomer constituting the copolymer of an epoxy group-containing monomer and a styrene-based monomer include, for example, glycidyl (meth)acrylate and glycidyl itaconate, and preferably glycidyl methacrylate and glycidyl acrylate, and particularly preferably glycidyl methacrylate. Examples of the styrene-based monomer include styrene, α-methylstyrene, p-methylstyrene, vinylxylene, ethylstyrene, dimethylstyrene, p-tert-butylstyrene, vinylnaphthalene, methoxystyrene, monobromostyrene, dibromostyrene, fluorostyrene, and tribromostyrene, and more preferably styrene and α-methylstyrene, and particularly preferably styrene. Specific examples of copolymers of epoxy group-containing monomers and styrene-based monomers include glycidyl (meth)acrylate-styrene copolymers and glycidyl (meth)acrylate-styrene-methyl (meth)acrylate, etc., which tend to have improved adhesion to epoxy-based adhesives and are therefore particularly preferred.
[0147] The epoxy equivalent of the epoxy compound used in the present embodiment is preferably 100 g / eq or more, more preferably 150 g / eq or more, and is preferably 1000 g / eq or less, more preferably 300 g / eq or less, and even more preferably 250 g / eq or less.
[0148] When the resin composition of the present embodiment contains two or more kinds of epoxy compounds, the epoxy equivalent is a value (weighted average value) obtained by multiplying the epoxy equivalent of each epoxy compound by the mass fraction of each epoxy compound.
[0149] In addition to the above, the epoxy compound can be referred to in paragraphs 0038 to 0050 of JP-A-2020-199755 and paragraph 0043 of JP-A-2020-125468, the contents of which are incorporated herein by reference.
[0150] When the resin composition of the present embodiment contains an epoxy compound, the content is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, relative to 100 parts by mass of the polybutylene terephthalate resin. The upper limit of the content of the epoxy compound is preferably 15 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 7.0 parts by mass or less, and even more preferably 2.0 parts by mass or less, relative to 100 parts by mass of the polybutylene terephthalate resin.
[0151] The resin composition of the present embodiment may contain only one type of epoxy compound, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0152] <Stabilizer> The resin composition of the present embodiment may contain a stabilizer (a light stabilizer and / or a heat stabilizer).
[0153] The stabilizer preferably contains one or more compounds selected from the group consisting of thioether-based compounds, hindered phenol-based compounds, and phosphite-based compounds, and more preferably a hindered phenol-based compound.
[0154] In the present embodiment, it is also preferable to use two or more of the thioether-based compounds, the hindered phenol-based compounds, and the phosphite-based compounds in combination as necessary.
[0155] As the thioether-based compound, any conventionally known sulfur atom-containing compound can be used, and among them, thioethers are preferred. By including the thioether-based compound in the resin composition of the present embodiment, the appearance of the molded product tends to be improved and the thermal stability tends to be improved. Specific examples include didodecylthiodipropionate, ditetradecylthiodipropionate, dioctadecylthiodipropionate, pentaerythritol tetrakis(3-dodecylthiopropionate), 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-(dodecylthio)propionate], thiobis(N-phenyl-β-naphthylamine), 2-mercaptobenzothiazole, 2-mercaptobenzimidazole, tetramethylthiuram monosulfide, tetramethylthiuram disulfide, nickel dibutyldithiocarbamate, nickel isopropylxanthate, and trilauryltrithiophosphite. Among these, 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-(dodecylthio)propionate] is preferable. Commercially available products include "Seenox 412S" manufactured by Shipro Chemical Co., Ltd. and "Adekastab AO-412S" manufactured by ADEKA Corporation.
[0156] Examples of hindered phenol compounds include pentaerythritol tetrakis (3-(3,5-di-t-butyl-4-hydroxyphenyl) propionate), octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, thiodiethylene bis (3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), pentaerythritol tetrakis (3-(3,5-di-neopentyl-4-hydroxyphenyl) propionate), 1,3,5-trimethyl-2,4,6-tris (3,5-di-tert-butyl-4-hydroxybenzyl) benzene, etc. Among these, pentaerythritol tetrakis (3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) and octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate are preferred. Commercially available products include those manufactured by ADEKA Corporation under the trade names "ADEKA STAB AO-60" and "ADEKA STAB AO-330."
[0157] The phosphite compound is preferably a compound represented by the formula: R 2 OP(OR 3 )(OR 4 ) (In the formula, R 2 , R 3 and R 4 are each a hydrogen atom, an alkyl group having 1 to 30 carbon atoms, or an aryl group having 6 to 30 carbon atoms, and R 2 , R 3 and R 4 At least one of the groups is an aryl group having 6 to 30 carbon atoms.)
[0158] Examples of the compound include compounds represented by the following formula:
[0159] Examples of the phosphite compound include triphenyl phosphite, tris(nonylphenyl)phosphite, dilauryl hydrogen phosphite, triethyl phosphite, tridecyl phosphite, tris(2-ethylhexyl)phosphite, tris(tridecyl)phosphite, tristearyl phosphite, diphenyl monodecyl phosphite, monophenyl didecyl phosphite, diphenyl mono(tridecyl)phosphite, tetraphenyl dipropylene glycol diphosphite, tetraphenyl tetra(tridecyl)pentaerythritol tetraphosphite, hydrogenated bisphenol A phenol phosphite polymer, diphenyl hydrogen phosphite, 4,4'-butylidene-bis(3-methyl-6-tert-butylphenyl di(tridecyl)phosphite), tetra(tridecyl) 4,4'-isopropyl phosphite, tetra(tridecyl) ... propylidenediphenyl diphosphite, bis(tridecyl)pentaerythritol diphosphite, bis(nonylphenyl)pentaerythritol diphosphite, dilauryl pentaerythritol diphosphite, distearyl pentaerythritol diphosphite, tris(4-tert-butylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, hydrogenated bisphenol A pentaerythritol phosphite polymer, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, 2,2'-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, and the like. Among these, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite is preferable. An example of a commercially available product is "ADEKA STAB PEP-36" manufactured by ADEKA Corporation.
[0160] Other examples of stabilizers include the following: JP 2021-063196 A, paragraphs 0067 to 0075; JP 2018-070722 A, paragraphs 0046 to 0057; JP 2019-056035 A, paragraphs 0030 to 0037; and WO 2017 / 038949 A, paragraphs 0066 to 0078. The contents of these are incorporated herein by reference.
[0161] The content of the stabilizer in the resin composition of the present embodiment is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more, relative to 100 parts by mass of polybutylene terephthalate resin. By making it equal to or more than the lower limit, the effect of suppressing thermal deterioration and oxidative deterioration of the resin during melt kneading, molding, and use as a molded body tends to be improved, and heat resistance tends to be improved. In addition, the upper limit of the content of the stabilizer is preferably 1.0 parts by mass or less, more preferably 0.8 parts by mass or less, more preferably 0.6 parts by mass or less, even more preferably 0.5 parts by mass or less, and even more preferably 0.4 parts by mass or less, relative to 100 parts by mass of polybutylene terephthalate resin. By making it equal to or less than the upper limit, it tends to be possible to effectively suppress adverse effects on appearance and physical properties due to aggregation of additives such as stabilizers, and it tends to be possible to suppress discoloration of the resin composition.
[0162] The resin composition of the present embodiment may contain only one type of stabilizer, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0163] <Release agent> The resin composition of the present embodiment preferably contains a release agent.
[0164] As the release agent, a wide variety of known release agents can be used, and examples thereof include aliphatic carboxylic acid amides, aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15,000, and polysiloxane-based silicone oils. Of these, aliphatic carboxylic acid amides and / or aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15,000 are preferred.
[0165] Examples of the aliphatic carboxylic acid amide include compounds obtained by a dehydration reaction between a higher aliphatic monocarboxylic acid and / or a polybasic acid and a diamine.
[0166] As the higher aliphatic monocarboxylic acid, saturated aliphatic monocarboxylic acids and hydroxycarboxylic acids having 16 or more carbon atoms are preferred, and examples thereof include palmitic acid, stearic acid, behenic acid, montanic acid, and 12-hydroxystearic acid.
[0167] Examples of polybasic acids include aliphatic dicarboxylic acids such as malonic acid, succinic acid, adipic acid, sebacic acid, pimelic acid, and azelaic acid; aromatic dicarboxylic acids such as phthalic acid and terephthalic acid; and alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid and cyclohexylsuccinic acid.
[0168] Examples of diamines include ethylenediamine, 1,3-diaminopropane, 1,4-diaminobutane, hexamethylenediamine, metaxylylenediamine, tolylenediamine, paraxylylenediamine, phenylenediamine, and isophoronediamine.
[0169] As the carboxylic acid amide compound, a compound obtained by polycondensation of stearic acid, sebacic acid, and ethylenediamine is preferred, and a compound obtained by polycondensation of 2 moles of stearic acid, 1 mole of sebacic acid, and 2 moles of ethylenediamine is more preferred. In addition to bisamide compounds obtained by reacting diamines and aliphatic carboxylic acids, such as N,N'-methylenebisstearamide and N,N'-ethylenebisstearamide, dicarboxylic acid amide compounds, such as N,N'-dioctadecylterephthalamide, can also be suitably used.
[0170] Examples of the aliphatic carboxylic acid include saturated or unsaturated aliphatic mono-, di- or tri-carboxylic acids. Here, the aliphatic carboxylic acid also includes alicyclic carboxylic acids. Among these, preferred aliphatic carboxylic acids are mono- or di-carboxylic acids having 6 to 36 carbon atoms, and more preferred are saturated aliphatic mono-carboxylic acids having 6 to 36 carbon atoms. Specific examples of such aliphatic carboxylic acids include palmitic acid, stearic acid, caproic acid, capric acid, lauric acid, arachic acid, behenic acid, lignoceric acid, cerotic acid, melissic acid, tetralinic acid, montanic acid, adipic acid, and azelaic acid.
[0171] In the ester of an aliphatic carboxylic acid and an alcohol, the aliphatic carboxylic acid may be the same as the aliphatic carboxylic acid. On the other hand, the alcohol may be, for example, a saturated or unsaturated monohydric or polyhydric alcohol. These alcohols may have a substituent such as a fluorine atom or an aryl group. Among these, a monohydric or polyhydric saturated alcohol having 30 or less carbon atoms is preferred, and an aliphatic or alicyclic saturated monohydric alcohol or an aliphatic saturated polyhydric alcohol having 30 or less carbon atoms is more preferred.
[0172] Specific examples of such alcohols include octanol, decanol, dodecanol, stearyl alcohol, behenyl alcohol, ethylene glycol, diethylene glycol, glycerin, pentaerythritol, 2,2-dihydroxyperfluoropropanol, neopentylene glycol, ditrimethylolpropane, and dipentaerythritol.
[0173] Specific examples of esters of aliphatic carboxylic acids and alcohols include beeswax (a mixture mainly composed of myricyl palmitate), stearyl stearate, behenyl behenate, stearyl behenate, glycerin monopalmitate, glycerin monostearate, glycerin distearate, glycerin tristearate, pentaerythritol monopalmitate, pentaerythritol monostearate, pentaerythritol distearate, pentaerythritol tristearate, pentaerythritol tetrastearate, and esters of montanic acid and polyfunctional alcohols.
[0174] Examples of the aliphatic hydrocarbons having a number average molecular weight of 200 to 15,000 include liquid paraffin, paraffin wax, microwax, polyethylene wax, Fischer-Tropsch wax, and α-olefin oligomers having 3 to 12 carbon atoms. The aliphatic hydrocarbons herein also include alicyclic hydrocarbons. The number average molecular weight of the aliphatic hydrocarbons is preferably 5,000 or less.
[0175] Examples of polyolefin waxes include polyethylene wax, polypropylene wax, and polyethylene propylene wax, with polyethylene wax being preferred.
[0176] The polyolefin wax may be unmodified or modified. Examples of modified polyolefin waxes include vinyl ester modified polyolefin wax, acid modified polyolefin wax, and oxidized polyolefin wax, and oxidized polyolefin wax is preferred. Oxidized polyolefin wax has excellent compatibility with polyalkylene terephthalate resins and tends to effectively suppress mold deposits in the resulting resin composition.
[0177] The oxidized polyolefin wax can be obtained by oxidizing the corresponding unmodified polyolefin wax. Examples of the oxidized polyethylene wax include Licowax (registered trademark) PED521, PED522, and PED121 manufactured by Clariant Chemicals; Ceridust (registered trademark) 3715, and the like.
[0178] In addition to the above, commercially available polyolefin waxes can be found in paragraph 0028 of JP-A-2022-140470, the contents of which are incorporated herein by reference.
[0179] The weight average molecular weight of the polyolefin wax is preferably 800 or more, more preferably 1,000 or more, even more preferably 1,500 or more, even more preferably 2,000 or more, and even more preferably 2,500 or more. By making it equal to or greater than the lower limit, the glowing time tends to be further shortened. In addition, the weight average molecular weight of the polyolefin wax is preferably 30,000 or less, more preferably 20,000 or less, even more preferably 15,000 or less, and even more preferably 10,000 or less. By making it equal to or less than the upper limit, the flowability of the resin composition during molding tends to be further improved.
[0180] The weight average molecular weight can be measured by GPC (gel permeation chromatography) using a Tosoh HLC-8320GPC EcoSEC, tetrahydrofuran as the solvent, three Shodex KF-G, KF-805L, and a KF-800D as columns, at a column temperature of 40°C and a flow rate of 1.2 mL / min, and is measured as a polystyrene equivalent value detected with a detector (UV-8320) at a detection wavelength of 254 nm.
[0181] In the case where the resin composition in the present embodiment contains two or more types of polyolefin waxes, the weight average molecular weight is the weight average molecular weight of the mixture.
[0182] The dropping point of the polyolefin wax is preferably 165°C or lower, more preferably 160°C or lower, even more preferably 155°C or lower, even more preferably 150°C or lower, even more preferably 145°C or lower, even more preferably 140°C or lower, even more preferably 135°C or lower, particularly more preferably 130°C or lower, and preferably 80°C or higher, more preferably 85°C or higher, even more preferably 85°C or higher, even more preferably 90°C or higher, and even more preferably 95°C or higher.
[0183] The dropping point is determined by heating a polyolefin wax until it changes from a solid to a liquid state and the temperature at which the first drop of molten material falls from a standard cup having an opening of 2.8 mm.
[0184] As for the release agent, in addition to the above, the descriptions in paragraphs 0063 to 0077 of JP 2018-070722 A and the descriptions in paragraphs 0090 to 0098 of JP 2019-123809 A can be referred to, the contents of which are incorporated herein by reference.
[0185] The resin composition of the present embodiment preferably contains 0.1 parts by mass or more of the release agent relative to 100 parts by mass of the polybutylene terephthalate resin, more preferably 0.5 parts by mass or more, and even more preferably 1.0 parts by mass or more, and preferably 5 parts by mass or less, more preferably 4 parts by mass or less, even more preferably 3 parts by mass or less, and even more preferably 2 parts by mass or less. By making it equal to or more than the lower limit, the releasability of the obtained molded article tends to be further improved. Also, by making it equal to or less than the upper limit, bleeding out of the obtained molded article can be effectively suppressed.
[0186] The resin composition may contain only one type of release agent, or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.
[0187] <Other ingredients> The resin composition of the present embodiment may contain other components in addition to the above-mentioned components as necessary, as long as the desired physical properties are not significantly impaired. The other components may be contained alone or in any combination and ratio of two or more.
[0188] Examples of other components include thermoplastic resins other than polybutylene terephthalate resin, resin additives, and fillers other than the above-mentioned fibrous reinforcing materials.
[0189] Specific examples of the resin additives include flame retardants, flame retardant assistants, colorants (pigments, dyes), nucleating agents, antistatic agents, antifogging agents, antiblocking agents, flow improvers, plasticizers, and dispersants.
[0190] The total amount of the resin additives is preferably 0% by mass or more and less than 10% by mass, more preferably 0% by mass or more and less than 5% by mass, and even more preferably 0% by mass or more and less than 3% by mass, based on 100% by mass of the resin composition.
[0191] Examples of thermoplastic resins other than polybutylene terephthalate resin include polyethylene terephthalate resin, polystyrene resin, and polycarbonate resin. The polyethylene terephthalate resin, polystyrene resin, and polycarbonate resin may be recycled products. In the present embodiment, an example is one in which recycled polyethylene terephthalate resin is included.
[0192] For the polyethylene terephthalate resin, the description in paragraphs 0061 to 0073 of JP 2023-112342 A can be referred to, the contents of which are incorporated herein by reference.
[0193] Regarding the polycarbonate resin, the description in paragraphs 0010 to 0014 of JP-A-2024-123765 can be referred to, the contents of which are incorporated herein by reference.
[0194] Regarding the polystyrene resin, the description in paragraphs 0021 to 0036 of JP 2024-122664 A can be referred to, the contents of which are incorporated herein by reference.
[0195] When the resin composition of this embodiment contains a thermoplastic resin other than polybutylene terephthalate resin, the content thereof may be 1 part by mass or more, 5 parts by mass or more, 10 parts by mass or more, 20 parts by mass or more, 30 parts by mass or more, or may be 100 parts by mass or less, 80 parts by mass or less, 60 parts by mass or less, 50 parts by mass or less, relative to 100 parts by mass of polybutylene terephthalate resin.
[0196] In one example of the resin composition of the present embodiment, the total amount of the polybutylene terephthalate resin, the fibrous reinforcing material, and the components blended as necessary is 100 mass %.
[0197] In the resin composition of this embodiment, the total of the polybutylene terephthalate resin, epoxy compound, stabilizer and fibrous reinforcing material preferably accounts for 90 mass% or more of the resin composition, more preferably 95 mass% or more, and may even be 100 mass%.
[0198] In another example of the resin composition of the present embodiment, the polybutylene terephthalate resin, the other thermoplastic resin other than polybutylene terephthalate resin (e.g., polyethylene terephthalate resin), the epoxy compound, the stabilizer and the fibrous reinforcing material preferably account for 90 mass% or more of the resin composition, more preferably 95 mass% or more, and may even be 100 mass%.
[0199] <Physical properties of resin composition> The resin composition of this embodiment has a melt volume rate (MVR) of 4 cm at 250°C and a load of 5 kgf. 3 / min or more is preferable, and 6cm 3 / min or more is preferable, and 9cm 3 More preferably, the rate is 15 cm / min or more. 3 / min or more is more preferable, and 25 cm 3 / min or more is even more preferable, and 3 / min or less is preferable, and 3 / min or less is more preferable, and 3 More preferably, the speed is 65 cm / min or less. 3 More preferably, it is 50 cm / min or less. 3 It is more preferable that the melt flow rate is equal to or more than the lower limit of the melt flow rate, and the melt flow rate is excellent in moldability. On the other hand, the melt flow rate is equal to or less than the upper limit of the melt flow rate, and the mechanical properties such as tensile strength are excellent.
[0200] The resin composition of this embodiment is molded into an ISO test piece (4 mm thick) and the tensile modulus measured according to ISO527-1 and ISO527-2 is preferably 5000 MPa or more, more preferably 6000 MPa or more, even more preferably 7000 MPa or more, even more preferably 8000 MPa or more, and even more preferably 9000 MPa or more, and the upper limit is not particularly set, but even if it is, for example, 100000 MPa or less, the required performance is sufficiently satisfied. By setting it to the lower limit or more, the rigidity of the molded article is improved, and the molded article tends to be made thinner and lighter.
[0201] The resin composition of this embodiment is molded into an ISO test piece (4 mm thick) and has a tensile strength measured according to ISO527-1 and ISO527-2 of preferably 70 MPa or more, more preferably 80 MPa or more, even more preferably 90 MPa or more, even more preferably 100 MPa or more, and even more preferably 120 MPa or more. There is no particular upper limit, but even if it is, for example, 500 MPa or less, the required performance is sufficiently satisfied. By making it equal to or greater than the lower limit, the mechanical strength of the molded article tends to be excellent.
[0202] The resin composition of this embodiment is molded into an ISO test piece (4 mm thick) and the tensile breaking strain measured according to ISO527-1 and ISO527-2 is preferably 0.5% or more, more preferably 0.8% or more, even more preferably 1.0% or more, even more preferably 1.2% or more, and even more preferably 1.5% or more, and the upper limit is not particularly set, but even if it is 10% or less, the required performance is sufficiently satisfied. By making it equal to or more than the lower limit, the toughness of the molded article tends to be excellent.
[0203] <Method of producing resin composition> The resin composition of this embodiment can be produced by a conventional method for preparing a resin composition (e.g., pellets). Usually, the components and various additives added as desired are thoroughly mixed together and then melt-kneaded in a single-screw or twin-screw extruder. The resin composition of this embodiment can also be prepared without premixing the components, or by premixing only a portion of the components, feeding the mixture to an extruder using a feeder and melt-kneading it. A portion of the components, such as a colorant, may be melt-kneaded with a thermoplastic resin to prepare a master batch, and then the remaining components may be blended therewith and melt-kneaded.
[0204] The fibrous reinforcing material is preferably fed from a side feeder midway through the cylinder of the extruder.
[0205] The heating temperature during melt kneading can be appropriately selected from the range of 220 to 300°C. If the temperature is too high, decomposition gas is likely to be generated, which may cause opacity. Therefore, it is desirable to select a screw configuration that takes into consideration shear heat generation, etc. In order to suppress decomposition during kneading and molding in the subsequent process, it is desirable to use an antioxidant or heat stabilizer.
[0206] <Method of manufacturing molded products> The molded article of this embodiment is molded according to a known method.
[0207] The manufacturing method of the molded product is not particularly limited, and any molding method generally used for resin compositions can be used. Examples of such molding methods include injection molding, ultra-high speed injection molding, injection compression molding, two-color molding, gas-assisted hollow molding, molding using a heat-insulating mold, molding using a rapid heating mold, foam molding (including supercritical fluid), insert molding, IMC (in-mold coating molding), extrusion molding, sheet molding, thermoforming, rotational molding, lamination molding, press molding, blow molding, etc., and among these, injection molding is preferred.
[0208] For details of the injection molding method, refer to paragraphs 0113 to 0116 of Japanese Patent No. 6183822, the contents of which are incorporated herein by reference.
[0209] The mold temperature during molding, such as injection molding, is preferably 40 to 150°C.
[0210] <Complex> The molded article obtained by molding the resin composition of this embodiment can be bonded to the same material or another member via an adhesive to form a composite. That is, the composite of this embodiment includes the molded article of this embodiment and an adhesive layer. The adhesive layer includes an adhesive (preferably an epoxy-based adhesive). Therefore, the resin composition and molded article of this embodiment can be used for adhesive bonding (preferably an epoxy-based adhesive bonding).
[0211] The other materials include materials containing at least one of resin (thermoplastic resin, thermosetting resin), metal, and glass.
[0212] An adhesive refers to a material that bonds two things together, and is usually a material that is not thermoplastic. Examples of the adhesive include epoxy adhesives, silicone adhesives, acrylic adhesives, urethane adhesives, and polyester adhesives, and epoxy adhesives are preferred, silicone adhesives, and urethane adhesives are more preferred. Only one type of adhesive may be used, or two or more types may be mixed and used. The thickness of the adhesive layer is preferably 0.01 μm or more, more preferably 0.1 μm or more, and is preferably 10,000 μm or less, and more preferably 5,000 μm or less.
[0213] <Application> The resin composition or pellets of the present embodiment are used as molded articles formed therefrom. The applications of the resin composition, pellets, or molded articles are not particularly limited, but are preferably for vehicle parts or electric / electronic parts.
[0214] Vehicle parts include lamp housings, reflectors, bezels, extensions, connectors, ECU cases, housings for in-vehicle cameras and millimeter-wave radars, battery cases, and sensor housings.
[0215] Examples of electric and electronic components include display devices such as personal computers, game consoles and televisions, printers, copy machines, scanners, fax machines, electronic organizers and PDAs, electronic desk calculators, electronic dictionaries, cameras, video cameras, mobile phones, battery packs, drives and readers for recording media, mice, numeric keypads, CD players, MD players, portable radio and audio players, housings, covers, keyboards, buttons, switch components, power meter cases, battery cases, battery transport trays, relays, sensors, actuators, terminal switches and grill cooking appliance parts. EXAMPLES
[0216] The present invention will be described in more detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below.
[0217] If the measuring instruments used in the examples are difficult to obtain due to discontinuation or the like, measurements can be made using other instruments with equivalent performance.
[0218] 1.Raw materials The following raw materials were used:
[0219] [Table 1]
[0220] Details of PBT-1 to PBT-3 are as follows.
[0221] [Table 2]
[0222] <Intrinsic viscosity (IV)> The intrinsic viscosity was measured by the following method.
[0223] Pellets of polybutylene terephthalate resin were dissolved in a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (mass ratio 1 / 1) by stirring at 110°C for 1 hour to a concentration of 1.00 g / dL. The solution was then cooled to 30°C. The time it took for the sample solution and the solvent alone to fall at 30°C was measured using a fully automatic solution viscometer, and the intrinsic viscosity was calculated using the formula:
[0224] Intrinsic viscosity=((1+4K H η sp ) 0.5 -1) / (2K H C) Here, η sp = η / η0-1, where η is the time it takes for the sample solution to fall, η0 is the time it takes for the solvent alone to fall, C is the concentration of the sample solution (g / dL), and K H is Huggins' constant. K H The value was 0.33. The unit is dL / g.
[0225] The fully automatic solution viscometer used was a product of Shibayama Scientific Co., Ltd.
[0226] <Melting point (Tm) and crystallization temperature (Tc)> The melting point (Tm) and crystallization temperature (Tc) of polybutylene terephthalate resin were measured using a differential scanning calorimeter (DSC) based on JIS K7121. The temperature was raised from 40°C to 300°C at a heating rate of 20°C / min under a nitrogen atmosphere, and after holding at 300°C for 3 minutes, the temperature was lowered to 40°C at a heating rate of -20°C / min. This was considered as one cycle. The temperature of the maximum peak due to crystallization during cooling was taken as the crystallization temperature Tc. The melting point Tm was calculated from the peak during melting. The unit is shown in °C.
[0227] The differential scanning calorimeter used was "DSC7020" manufactured by Hitachi High-Tech Science Corporation.
[0228] <ash content> The resin was incinerated for 3 hours in an electric furnace at 500°C to burn off only the resin component, and the ash content was measured based on the mass of the residue. The ash content in the polyalkylene terephthalate resin was expressed in mass%.
[0229] The electric furnace used was "Electric Muffle Furnace KM-28" manufactured by Toyo Seisakusho Co., Ltd.
[0230] <Terminal carboxyl group concentration (acid value)> The terminal carboxyl group concentration of the polybutylene terephthalate resin was determined by dissolving 0.5 g of the polybutylene terephthalate resin in 25 mL of benzyl alcohol and titrating it with a 0.01 mol / L benzyl alcohol solution of sodium hydroxide. The unit is μmol / g (μeq / g).
[0231] <Terminal hydroxyl group concentration> The terminal hydroxyl group concentration of polyalkylene terephthalate resin was measured by dissolving 25 mg of sample in a vial in 0.75 mL of a mixed solvent of deuterated chloroform / hexafluoroisopropanol (volume ratio: 7 / 3) containing a trace amount of TMS (tetramethylsilane), adding 25 μL of deuterated pyridine, and transferring to an NMR sample tube with an outer diameter of 5 mm. 1H NMR spectra were measured using a Bruke AVANCE NEO 600 spectrometer. The resonance frequency was 600, 1 MHz, the flip angle was 45°, the data acquisition time was 3 s, the pulse repetition time was 10 s, the number of accumulations was 16, and the temperature was 25°C.
[0232] The unit is μmol / g.
[0233] <Terminal vinyl group concentration> The terminal vinyl group concentration of the polyalkylene terephthalate resin was measured under the same conditions as the terminal hydroxyl group concentration of the polyalkylene terephthalate resin, and the unit is μmol / g.
[0234] <Weight average molecular weight (Mw) and number average molecular weight (Mn)> The weight average molecular weight and number average molecular weight of the resin were measured using a Tosoh HLC-8320. The polyalkylene terephthalate resin was weighed, and a predetermined amount of HFIP (hexafluoro-2-propanol) and 10 mM-CF3COONa eluent was added, and the resin was left to dissolve at room temperature overnight. The resin was then filtered through a 0.45 μm PTFE cartridge filter. The molecular weight (Mw, Mn) of the dissolved sample (filtrate) was measured by GPC. The calibration curve was a third-order approximation curve using standard PMMA, and the molecular weight was calculated in terms of PMMA.
[0235] For the GPC measurement, a Tosoh TSKgel GMHhr-M column (manufactured by Tosoh) was used.
[0236] <Active titanium parameter X and active titanium ratio α> Five capillaries with an inner diameter of 5 mm were filled with the polybutylene terephthalate resin (pellets) powder obtained above. Next, the contents were thoroughly replaced with nitrogen, and the capillaries were immersed in an oil bath precisely controlled at 245°C (temperature T), removed over time, and quenched with liquid nitrogen. The contents were then removed, and the terminal carboxyl group concentration and terminal hydroxyl group concentration were determined. Using these values, the active titanium ratio α was calculated from equations (1), (2), and (3).
[0237]
number
[0238]
number
[0239] α=X / M...Equation (3) (In formula (3), X is the active titanium parameter, and [M] is the titanium element concentration (ppm by mass) in the polybutylene terephthalate resin.)
[0240] The evaluation of the change in the terminal carboxyl group concentration over time is performed under a nitrogen atmosphere to prevent the influence of oxygen. In addition, if the water concentration in the polybutylene terephthalate resin to be evaluated is high, hydrolysis reactions occur frequently, making it difficult to accurately grasp the decomposition behavior involving catalytic activity not due to hydrolysis, so the water concentration is preferably low and is performed at 300 mass ppm or less. The temperature is 245°C. Under such heat treatment conditions, the decrease in number average molecular weight due to reactions other than the hydrolysis reaction caused by the water contained in the polybutylene terephthalate resin can be ignored, and the increase in the terminal carboxyl group concentration due to the hydrolysis reaction can be considered to be equal to the increase in the terminal hydroxyl group concentration before and after the heat treatment, so the change in the terminal carboxyl group concentration due to thermal decomposition reactions other than the hydrolysis reaction is calculated using the following formula (4).
[0241] Formula (4)
[0242]
number
[0243] <Measurement of the amount of metal elements> Qualitative / semi-quantitative analysis of metal elements (Al, Fe) in polybutylene terephthalate resin was performed by ICP emission spectrometry. In this case, 200 mg of sample was weighed out as pretreatment, and Kjeldahl wet decomposition (sulfuric acid / nitric acid, sulfuric acid / hydrogen peroxide) was performed, and the volume was adjusted to 50 mL. Then, ICP emission spectrometry was performed by acid concentration matching single point calibration method. The unit is shown in ppm by mass.
[0244] ICP emission analysis was performed using a ThermoThromo Fisher Scientific "iCAP7600duoiCAP76000uo" by axial / radial photometry.
[0245] <Total nitrogen content in polybutylene terephthalate resin (TN (total nitrogen content))> The resin was burned in an argon and oxygen atmosphere, and the generated combustion gas was measured with a trace nitrogen analyzer using the vacuum chemiluminescence method. At that time, aniline dissolved in toluene was used as a standard sample.
[0246] (Apparatus) Total nitrogen analyzer: TN-2100H type manufactured by Nitto Seiko Analytech Co., Ltd. (Total sulfur content (S-N (total sulfur content)) in polybutylene terephthalate resin) The resin and the combustion aid were collected in a magnetic boat, heated in a quartz tubular furnace, and the S component in the combustion gas was absorbed with an aqueous H2O2 solution. SO4 in the absorption solution 2- was measured with an ion chromatograph.
[0247] (Apparatus) Quartz tubular furnace: AQF2100H type manufactured by Nitto Seiko Analytech Co., Ltd. Ion chromatogram: ICS-1600 type manufactured by Thermo Fisher Scientific (Measurement of Ti concentration, Na concentration, Ca concentration) The qualitative / semi-quantitative analysis (μg / g) of Ti, Na, and Ca in polybutylene terephthalate resin was performed by ICP emission spectrometry. In this case, 200 mg of the sample was weighed as a pretreatment, Kjeldahl wet digestion (sulfuric acid / nitric acid, sulfuric acid / hydrogen peroxide) was performed, and the volume was fixed to 50 mL. Subsequently, ICP emission analysis was performed by the acid concentration matching single-point calibration method. The unit was shown in mass ppm.
[0248] ICP emission analysis was performed using "iCAP7600duoiCAP76000uo" manufactured by ThermoThrmo Fisher Scientific, with axial / radial photometry.
[0249] Examples 1 to 4, Comparative Examples 1 to 3 (Compound) The components shown in Table 1 were mixed uniformly in a tumbler mixer in the ratios shown in Table 3 or Table 4 (each component in Table 3 or Table 4 is shown in parts by mass). The mixture obtained was fed to a twin-screw extruder ("TEX30α" manufactured by Japan Steel Works, Ltd.) from the main feed port. The cylinder temperature setting of the first kneading section was set to 260°C, and the glass fibers were fed from a side feeder. The resin composition was melt-kneaded under the conditions of a cylinder temperature setting of 220°C after the addition of the glass fibers and a screw rotation speed of 200 rpm, and was quenched in a water tank and pelletized using a pelletizer to obtain pellets of the resin composition.
[0250] <Measurement of MVR of resin composition> The melt volume rate of the pellets of the resin composition obtained above was measured in accordance with ISO1133 at 250°C and a load of 5 kgf. The unit is cm 3 / 10min.
[0251] <Adhesive strength> The resin pellets obtained above were dried at 120°C for 5 hours, and then ISO multipurpose test pieces (thickness 4 mm) were injection molded using an injection molding machine (Japan Steel Works, Ltd., "J-85AD-60H") under conditions of a cylinder temperature of 250°C and a mold temperature of 80°C.
[0252] A 20mm x 20mm square adhesive application area was created by attaching Nitto Corporation's NITOFLON adhesive tape (10mm wide x 0.18mm thick) to the chuck of the obtained ISO multipurpose test piece. After that, a one-part epoxy adhesive, heat-curing adhesive was applied to this area, and the chuck of another ISO multipurpose test piece made of the same material was attached to it and fixed with a binder clip, and the adhesive was treated under the specified curing conditions to bond them together.
[0253] A tensile test was carried out using Shimadzu Corporation's AUTOGRAPH AGS-X 10 kN at a tensile speed of 5 mm / min to measure the adhesive strength (unit: N).
[0254] <Tensile properties> The pellets obtained above were dried at 110°C for 5 hours, and then injection molded into 4 mm thick ISO test pieces using an injection molding machine (Japan Steel Works, Ltd., "J85AD") under conditions of a cylinder temperature of 250°C and a mold temperature of 80°C.
[0255] For the ISO test pieces (4 mm thick) obtained above, the tensile modulus (unit: MPa), tensile strength (unit: MPa), and tensile breaking strain (unit: %) were measured in accordance with ISO527-1 and ISO527-2.
[0256] <Amount of gas generated> The amount of gas (THF) generated in the resin composition was measured according to the following method.
[0257] The pellets of the resin composition were heated at 150° C. for 10 minutes, and the resulting gas was analyzed. The gas analysis was performed by headspace gas chromatography. The amount of generated gas (THF) was measured.
[0258] Gas analysis was performed using a Nexis GC-2030 manufactured by Shimadzu Corporation.
[0259] [Table 3]
[0260] [Table 4]
[0261] As is clear from the above results, the molded articles formed from the resin composition of the present invention had high adhesive strength to an epoxy adhesive (Examples 1 to 4). In addition, various mechanical properties were also excellent. Furthermore, the amount of gas contained in the pellets could be reduced.
[0262] In contrast, when polybutylene terephthalate resin with a small total nitrogen content was used (Comparative Examples 1 to 3), the adhesive strength to the epoxy adhesive was low, and the amount of gas generated in the pellets was also large.
Claims
1. The composition comprises a polybutylene terephthalate resin and at least one selected from the group consisting of an inorganic filler, a release agent, and a stabilizer; The polybutylene terephthalate resin has a total nitrogen element content of 0.1 to 3000 ppm by mass, and an active titanium parameter X shown below is 25 or less. [0010] [0025]
2. The inorganic filler is contained in an amount of 10 to 150 parts by mass relative to 100 parts by mass of the polybutylene terephthalate resin, The inorganic filler is a fibrous reinforcing material; The resin composition according to claim 1.
3. The resin composition according to claim 1 or 2, further comprising a release agent and / or a stabilizer.
4. The resin composition according to claim 1 or 2, wherein the active titanium parameter X is 12 or less.
5. The resin composition according to claim 1 or 2, wherein the polybutylene terephthalate resin contains 30 to 500 ppm by mass of titanium element.
6. The resin composition according to claim 1 or 2, wherein the polybutylene terephthalate resin has a terminal carboxyl group concentration of 25 μmol / g or more.
7. The resin composition according to claim 1 or 2, further comprising a recycled polyethylene terephthalate resin.
8. The resin composition according to claim 1 or 2, wherein the polybutylene terephthalate resin has a total sulfur element content of 0.1 to 100 ppm by mass.
9. The resin composition according to claim 1 or 2, wherein the polybutylene terephthalate resin has a terminal vinyl group concentration of 1 to 15 μmol / g.
10. The polybutylene terephthalate resin has dicarboxylic acid units and diol units, and 80 mol % or more of the total dicarboxylic acid units are terephthalic acid units derived from fossil resources, and 80 mol % or more of the total diol units are 1,4-butanediol units derived from fossil resources. The resin composition according to claim 1 or 2.
11. The resin composition according to claim 1 or 2, wherein the polybutylene terephthalate resin has an Mw / Mn ratio of 2.1 or more.
12. The resin composition according to claim 1 or 2, wherein the polybutylene terephthalate resin comprises a recycled product.
13. The resin composition according to claim 1 or 2, further comprising an epoxy compound.
14. The inorganic filler is contained in an amount of 10 to 150 parts by mass relative to 100 parts by mass of the polybutylene terephthalate resin, The inorganic filler is a fibrous reinforcing material, containing a release agent and / or a stabilizer, The active titanium parameter X is 12 or less; The polybutylene terephthalate resin contains 30 to 500 ppm by mass of titanium element, The polybutylene terephthalate resin has a terminal carboxyl group concentration of 25 μmol / g or more; In addition, it contains recycled polyethylene terephthalate resin, The polybutylene terephthalate resin has a total sulfur element content of 0.1 to 100 ppm by mass, The polybutylene terephthalate resin has a terminal vinyl group concentration of 1 to 15 μmol / g, The polybutylene terephthalate resin has dicarboxylic acid units and diol units, and 80 mol % or more of the total dicarboxylic acid units are terephthalic acid units and 80 mol % or more of the total diol units are 1,4-butanediol units. The polybutylene terephthalate resin has an Mw / Mn ratio of 2.1 or more, The resin composition of claim 1 , wherein the polybutylene terephthalate resin comprises a recycled product.
15. The resin composition according to claim 14, further comprising an epoxy compound.
16. The polybutylene terephthalate resin has dicarboxylic acid units and diol units, and 80 mol% or more of the total dicarboxylic acid units are terephthalic acid units derived from fossil resources, and 80 mol% or more of the total diol units are 1,4-butanediol units derived from fossil resources. The resin composition according to claim 14 or 15.
17. 16. The resin composition according to claim 1, 2, 14 or 15, which is for use in bonding with epoxy adhesives.
18. 16. Pellets of the resin composition according to claim 1, 2, 14 or 15.
19. A molded article molded from the resin composition according to claim 1, 2, 14 or 15.
20. A molded article made from the pellets according to claim 18.
21. 20. A composite comprising the molded article of claim 19 and an adhesive layer, the adhesive layer comprising an epoxy-based adhesive.
Citation Information
Patent Citations
Polybutylene terephthalate resin composition
JP2018203932A
Reinforced polyester structural components
WO2019217680A1
Resin composition and method for producing same
WO2020246335A1